The dynamic of brain rhythms after neurofeedback course - O. V. Kaigorodceva; V. G. Tristan; I. G. Talamova (Бюллетень сибирской медицины)
In this article there is comparative analysis of cerebrum biopotentials of sportsmen in different periods after the end of neurofeedback course. It was revealed the character of late effects has depended on success of the training and period it’s end. For sportsmen studying increase the alpha-rhythm power arbitrarily it is typical: the alpha-rhythm power of both hemispheres increased strait a way after training with closed eyes and during 3 months with opened eyes which in a year was being slow decreased. The values of β- and θ-rhythms were slow decreased in 6—12 months. For sportsmen how were held training unsuccessfully it is typical increasing of alpha-rhythm power in a year, which didn’t depend on decreasing of visual afferentation. The changings of θ-rhythm had wavy character, the β-rhythm power was being decreased.